Assessing the environmental benefit of palladium-based single-atom heterogeneous catalysts for Sonogashira coupling - Faust Akl, D; Poier, D; D'Angelo, S C; Araújo, T P; Tulus, V; Safonova, O V; Mitchell, S; Marti, R; Guillén-Gosálbez, G; Pérez-Ramírez, J (Green chemistry : an international journal and green chemistry resource : GC, 2022)
The Pd-Cu catalysed Sonogashira coupling of terminal alkynes and aryl halides is a cornerstone synthetic strategy for C-C bond formation. Homogeneous organometallic systems conventionally applied are typically not reusable and require efficient downstream Pd removal steps for product purification, making it challenging to fully recover the precious metal. A holistic cradle-to-gate life cycle assessment (LCA) unveils that process footprint can be improved up to two orders of magnitude from repeated catalyst reuse. New classes of heterogeneous catalysts based on isolated metal atoms (single-atom catalysts, SACs) demonstrate promising potential to synergise the benefits of solid and molecular catalysts for efficient Pd utilisation. Here we show that using Pd atoms anchored on nitrogen-doped carbon permits full recovery of the metal and reuse of the catalyst over multiple cycles. A hybrid process using the Pd-SAC with a homogeneous CuI cocatalyst is more effective than a fully heterogeneous analogue based on a bimetallic Pd-Cu SAC, which deactivates severely due to copper leaching. In some scenarios, the LCA-based metrics demonstrate the footprint of the hybrid homogeneous-heterogeneous catalytic process is leaner than the purely homogeneous counterpart already upon single reuse. Combining LCA with experimental evaluation will be a useful guide to the implementation of solid, reusable catalysts for sustainable organic transformations.